KEEPING TRACK OF INMATES. (American City & County, 2011)
The article reports that Microsoft Corp.'s Dynamics CRM platform allowed the Illinois Department of Corrections (DOC) to integrate paper and electronic documents on each offender into one form. The lead developer on the project was a former prison guard who recently received his bachelor's degree in computer sciences. Microsoft provided technical training and installation support.